2013
DOI: 10.9790/2402-0310110
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation and bioaccumulation of arsenic by Brevibacillus brevis isolated from arsenic contaminated region of West Bengal

Abstract: Microorganisms influence the fate of metals in environment. Increasing anthropogenic and geogenic activity had increase the risk of arsenic pollution and this has forced the future research area to involve microbes-metal toxicity to achieve bioremediation. The present study deals with the role of arsenite transforming bacteria and incorporates them into remediation design. Sample was collected from Haringhata in Nadia district which is a known arsenic contaminated zone. Out of six isolated bacteria one bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…However, another study (Banerjee et al 2013) reported that Brevibacillus brevis Strain S1 had tolerances of 500 mg L -1 and 1000 mg L -1 for arsenate and arsenite, respectively. This difference is likely due to the reduced condition of the soil, making arsenite predominant and thus, making the strain more tolerant of arsenite than of arsenate.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, another study (Banerjee et al 2013) reported that Brevibacillus brevis Strain S1 had tolerances of 500 mg L -1 and 1000 mg L -1 for arsenate and arsenite, respectively. This difference is likely due to the reduced condition of the soil, making arsenite predominant and thus, making the strain more tolerant of arsenite than of arsenate.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, in respect to bioaccumulation of arsenic, it was found that all three bacterial strains can accumulate arsenic but SS11 accumulated the most. Banerjee et al (2013) reported that Brevibacillus brevis strain S1 can accumulate a maximum of 27.1 mg L -1 of arsenic after 3 days of incubation. The heavy metal toxicity test also revealed that SS11 had greater metal tolerance than the other two strains, although all three showed tolerance against different heavy metals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Release of As into the environment occurs predominantly due to both natural weathering processes and biological activities, thus broadening the As cycle with time and creating a global threat (Nickson et al, 2000;Smith et al, 2000;Chakraborty et al, 2002;Lloyd, 2002;Mukhopadhyay et al, 2002;Nordstrom, 2002;Bhattacharya et al, 2009;Banerjee et al, 2013). The most common available inorganic forms of As are arsenate [As(V)] and arsenite [As(III)] (Buchet and Lauwerys, 1981;Leonard, 1991;Mukhopadhyay et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…The occurrence of different As forms and their mobility in soil depends on several environmental factors (Woolson, 1977). Groundwater with As at hazardous concentrations is widely used for domestic purposes and for irrigating field crops as well in different regions, especially in the Bengal-delta, China, Taiwan, Vietnam, the US, Argentina, Chile, and Mexico (Brammer, 2008;Banerjee et al, 2013). Irrigation of agricultural fields with such groundwater increases the concentration of As in crop fields, creating potential risk for biomagnification by entering into the food chain (Rahman et al, 2007;2008;Bhattacharya et al, 2009).…”
Section: Introductionmentioning
confidence: 99%